Autoantibodies in COVID‐19 correlate with antiviral humoral responses and distinct immune signatures. Issue 8 (8th April 2022) - Taeschler, Patrick; Cervia, Carlo; Zurbuchen, Yves; Hasler, Sara; Pou, Christian; Tan, Ziyang; Adamo, Sarah; Raeber, Miro E.; Bächli, Esther; Rudiger, Alain; Stüssi‐Helbling, Melina; Huber, Lars C.; et al.
Abstract: Background: Several autoimmune features occur during coronavirus disease 2019 (COVID‐19), with possible implications for disease course, immunity, and autoimmune pathology. In this study, we longitudinally screened for clinically relevant systemic autoantibodies to assess their prevalence, temporal trajectory, and association with immunity, comorbidities, and severity of COVID‐19. Methods: We performed highly sensitive indirect immunofluorescence assays to detect antinuclear antibodies (ANA) and antineutrophil cytoplasmic antibodies (ANCA), along with serum proteomics and virome‐wide serological profiling in a multicentric cohort of 175 COVID‐19 patients followed up to 1 year after infection, eleven vaccinated individuals, and 41 unexposed controls. Results: Compared with healthy controls, similar prevalence and patterns of ANA were present in patients during acute COVID‐19 and recovery. However, the paired analysis revealed a subgroup of patients with transient presence of certain ANA patterns during acute COVID‐19. Furthermore, patients with severe COVID‐19 exhibited a high prevalence of ANCA during acute disease. These autoantibodies were quantitatively associated with higher SARS‐CoV‐2‐specific antibody titers in COVID‐19 patients and in vaccinated individuals, thus linking autoantibody production to increased antigen‐specific humoral responses. Notably, the qualitative breadth of antibodies cross‐reactive with other coronaviruses was comparable in ANA‐positive and ANA‐negative individuals during acute COVID‐19. In autoantibody‐positive patients, multiparametric characterization demonstrated an inflammatory signature during acute COVID‐19 and alterations of the B‐cell compartment after recovery. Conclusion: Highly sensitive indirect immunofluorescence assays revealed transient autoantibody production during acute SARS‐CoV‐2 infection, while the presence of autoantibodies in COVID‐19 patients correlated with increased antiviral humoral immune responses and inflammatory immune signatures. Abstract : In a multicentric cohort of 175 COVID‐19 patients, 11 vaccinated individuals, and 41 unexposed controls, we measured ANA and ANCA, along with serum proteomics and virome‐wide serological profiling. Paired analysis revealed the transient presence of ANA patterns and ANCA during acute COVID‐19. The presence of autoantibodies correlated with increased virus‐specific humoral immune responses and a proinflammatory immune signature.Abbreviations: ANA, antinuclear antibodies; ANCA, antineutrophil cytoplasmic antibodies; COVID‐19, coronavirus disease 2019; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus type 2